Microscopic and macroscopic analysis of granular material behaviour in 3d flat-bottomed hopper by the discrete element method - Balevičius, R.; Kačianauskas, R.; Mróz, Z.; Sielamowicz, I. (Archives of Mechanics, 2007)
The paper presents the application of the discrete element method to modelling of granular material filling and discharge in 3D flat-bottomed hopper. A mathematical model, as well as the developed software code, operates with spherical visco-elastic non-cohesive frictional particles. The evolution of granular flow, internal forces and densification (rarefaction) are characterized by macroscopic parameters such as the discharge rates, the porosity fields and the wall pressures, as well as by microscopic evaluations in terms of coordination number, velocity patterns and inter-particle contact forces. It was shown that qualitative characterization of flow may be done even by relatively rough models with small number of particles, which required to be increased, however, for more precise description of the localized phenomena. Unsatisfactory evaluation of the stress peak during discharge is presented as an illustrative example. The main focus of the paper is the analysis of particle friction effect and the consistency of micro and macro-phenomena in the time-dependent flow process.